Student Satisfaction Towards the Use of F-Learn Services in Online Learning - Sophia Tri Satyawati (Jurnal Pendidikan dan Pengajaran, 2020)
This research aims to analyse the level of student satisfaction as the users of F-Learn service in online learning. The level of student satisfaction is measured by using the End User Computing Satisfaction (EUCS), model which includes five dimensions, namely: 1) content; 2) accuracy; 3) format; 4) ease of use; and 5) timeliness. The research method used was a survey with a quantitative descriptive approach. The sampling technique used was saturated sampling because the population used in this study was relatively small, namely 30 students as the users of the F-Learn service in online learning. The results show that the level of student satisfaction as users of the F-Learn service in all dimensions are at a good level. Meanwhile, the level of satisfaction in each dimension shows: 1) the content is at an acceptable level; 2) accuracy at the level is quite good; 3) format at an acceptable level, 4) ease of use at an acceptable level; and 5) timeliness at a good enough level. The findings of this study will be used as a measuring tool for the e-learning system (F-Learn) and as input for further development.